Genetic variation of liverleaf (Hepatica nobilis Schreb.) in Bavaria against the background of seed transfer guidelines in forestry and restoration. (April 2017) - Listl, Daniela; Poschlod, Peter; Reisch, Christoph
Abstract: The liver leaf, Hepatica nobilis (Ranunculaceae), is a perennial forest understory herb with specific habitat requirements, which occurs on calcareous soils in beech and oak forests. In Bavaria it can be found, therefore, only in four geographic regions, which are Franconia, the Franconian-Swabian Jura, the prealpine transitions region and the prealpine moraine belt with the Alps. In German forestry, provenance delineations are used since 1987. Similarly for herbs seed provenances and production areas are applied in commercial seed production and restoration. In this study we analyzed whether the genetic variation of H. nobilis reflects the geographic distribution of the species in Bavaria or the provenance delineations used for seed production. We applied AFLPs to study genetic variation within and between 24 populations of H. nobilis . Our analysis revealed high levels of genetic variation within and moderate variation between populations. Variation between seed production areas and seed provenances was low and comparable to the variation between geographic regions. Genetic variation within populations or rare fragments did not differ between production areas, provenances or geographic regions. A significant positive relation of genetic and geographic distances was present within 100 km. Pollination and seed dispersal seem mainly to happen within populations of the myrmecochorous H. nobilis, whereas long-distance dispersal is presumably occasional and random. Our study supports the relevance of dispersal traits for seed collections used in conservation. The protection of historically old beech and oak forests is exceedingly important to preserve the genetic variation of H. nobilis in Bavaria. Highlights: 24 liverleaf populations ( Hepatica nobilis ) were investigated with AFLPs in four geographic regions in Bavaria. Geographic regions, seed provenances or production areas are not reflected by genetic pattern. Pollination and seed dispersal seems mainly to happen within populations of the myrmecochorous H. nobilis . Protection of old forests is exceedingly important for the conservation of H. nobilis .